Imunoistoquímica de útero e cérvice de cadelas com diagnóstico de piometra - Volpato, R. [UNESP]; Martin, I. [UNESP]; Ramos, R. S. [UNESP]; Tsunemi, M. H. [UNESP]; Laufer-Amorim, Renee [UNESP]; Lopes, Maria Denise [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2012)
Analisou-se a piometra de 31 cadelas, de raças e idades variadas, sendo 25 cadelas com piometra de cérvice aberta e seis de cérvice fechada. Após ovariossalpingo-histerectomia, foram coletados fragmentos da cérvice e do útero para a avaliação imunoistoquímica. Foram analisados os receptores de estrógenos α e β, progesterona e colágenos I e III. Foram realizadas imunomarcações em diferentes regiões da cérvice, como o epitélio glandular, o epitélio luminal e o estroma glandular, assim como em diferentes regiões do útero, como o epitélio glandular e o estroma glandular. As imunomarcações de colágenos I e III foram realizadas nas regiões glandular e muscular da cérvice e do útero. Concentrações de receptores de progesterona foram maiores em cadelas com piometra fechada.

The pyometra in 31 bitches of different breeds and ages, 25 with pyometra cervix open and 6 closed cervix was analyzed. After the ovariohysterectomy procedure, samples were collected from the cervix and uterus to evaluate immunohistochemistry. For immunohistochemical evaluation estrogen receptors α and β, progesterone and collagen I and III were analyzed. Immunostainings were performed in different regions of the cervix such as glandular epithelium, luminal epithelium and glandular stroma, as well as in different regions of the uterus, such as glandular epithelium and glandular stroma. The immunostainings for collagen I and III were performed in muscular and glandular regions of the cervix and uterus. The concentration the progesterone receptors were elevated in bitches from the closed pyometra.
Immunohistochemical of the cervix and uterus of bitches diagnosed with pyometra
Keywords: cadela; imunoistoquímica; piometra; bitches; immunohistochemistry; pyometra